Pemberdayaan Remaja Melalui Peer Educator Rohani Remaja Katolik (Remaka) Paroki Santo Gregorius Agung Jambi Dalam Upaya Pencegahan COVID-19 - La Ode , Reskiaddin; Aswin, Budi; Siagian, Laurencus Butsi (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
The third of young adults are medically susceptible to the disease COVID-19. Community empowerment is a strategy in preventing COVID-19.This community service aims to train and form peer educators. There are several stages carried out in youth empowerment activities, including coordinating with the parish church of Saint Gregorius Agung Jambi, at the activity site, facilitators mobilizing activity participants, conveying the aims and objectives of activities, orders from peer educator teams, training and coaching peers, discussion and questions answer and evaluate activities. The results of this training helped improve adolescents' understanding of covid-19 and had formed 22 peer educators divided into eleven regions and as an agent of change in providing health information to the public.The need for socialization and ordering of peer educators in various regions as the pioneers of the Covid-19 task force. Keywords: Empowerment, Peer educator, Teenager